Design and construction of an anchored soil nail wall close to movement sensitive structures - Kho, A.K.; McAuley, M. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Legacy Way is a 4.6 km twin 12.4 m diameter road tunnel with approximately 3 km of surface connections to facilitate entering and exiting the tunnels. The new roadway bypasses Brisbane CBD to the west and will connect the Western Freeway at Toowong with the Inner City Bypass (ICB) at Kelvin Grove. As part of the Eastern surface connection works, a 12 m high × 55 m long soil nail and anchored wall retaining a soil and weathered rock slope was constructed as abutment support to the extended Inner Northern Busway (INB) bridge and Brisbane Grammar School (BGS) pedestrian bridge. The new abutment wall was an integral element of an overall solution that required addition of spans to the existing bridges and removal of the original Reinforced Soil Structure (RSS) abutments. The near vertical new abutment wall is located approximately 1 m in front of large diameter bored piles which support the extended bridge. Resistance of lateral pile loads and restriction of movement of the new bridge abutment were key constraints in the design. Bridge extension and construction of the new abutment wall has created sufficient space for a large buried drainage structure to carry floodwater outflow from nearby playing fields to an open channel further east. The buried drainage structure runs parallel to the ICB and supports a shared (pedestrian/bikeway) user path. This paper provides a commentary on the design approach adopted and construction issues encountered. Validation of the design through construction support and monitoring records is also summarised.